Demographic Processes in Developmentally Peripheral Areas of Hungary - János Pénzes; István Zoltán Pásztor; Patrik Tátrai (Stanovništvo)
The current study investigates the demographic processes and challenges of the Hungarian developmentally peripheral settlements. Demographic challenges can be regarded as important consequences of the social and economic disadvantages in spatial terms. However, the interrelating negative demographic tendencies cause even more backward situation blocking or hindering the development.